2021
DOI: 10.1186/s12889-021-12247-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for digital stress in German public administrations

Abstract: Objective As the digitization of the working world progresses, the demands on employees change. Not least, this is true for the setting of public administrations in Germany, which is currently affected by the transformation to E-Government. This study aims to identify and describe a risk cluster of digitally stressed employees in public administrations. Methods An online sample of 710 employees from three public administrations in North Rhine-Westp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The fact that the proportion of the risk cluster with regard to digital stress in 2020 is slightly lower than in Wrede et al (2021), is probably due, in addition to the below mentioned reasons, to the fact that here we ltered for employees who were already at least occasionally in the home o ce in 2020. In addition, the values of those employees who were in a department with fewer than ve respondents were dropped.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The fact that the proportion of the risk cluster with regard to digital stress in 2020 is slightly lower than in Wrede et al (2021), is probably due, in addition to the below mentioned reasons, to the fact that here we ltered for employees who were already at least occasionally in the home o ce in 2020. In addition, the values of those employees who were in a department with fewer than ve respondents were dropped.…”
Section: Discussionmentioning
confidence: 88%
“…The longitudinal study design and multivariate analysis enable reliable results, e.g., in terms of causation. In contrast to the previously published cross-sectional study based on the rst survey in the project "Health and Digital Transformation" (Wrede et al, 2021), the repeat survey avoided the risk of a transmitted variable bias. However, no evidence has been found for the impact of digital stress on emotions and disease within the study period.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the previously published cross-sectional studies based on the rst survey in the project "Health and Digital Transformation" [30,40,51,52], the repeat survey avoided the risk of a omitted variable bias. However, it still remains open to what extent the temporal development can actually be interpreted as a pandemic effect and whether, in concrete terms, it is a matter of personal-emotional or operational changes such as working from home, working more hours et cetera.…”
Section: Discussionmentioning
confidence: 99%
“…The organization of the departments and the work processes are a major cause of stress, while the interventions mostly address individual behavior rather than performance and organizational aspects. Wrede et al [40] found that within the setting having relatives to care for is a signi cant risk factor for digital stress.…”
Section: Hypothesis; Socio-demographic and Psychosomatic Correlates O...mentioning
confidence: 99%
“…Determinants of digital stress Wrede et al (2021) show that within the German public administration setting (among others) older age, feeling overwhelmed as well as resignation are signi cant risk factors for digital stress. When Gimpel et al (2018) examined "digital stress in Germany", they concluded that digital stress is more pronounced among younger workers.…”
Section: Digital Stress and Mental Strainmentioning
confidence: 99%